The origin of Islamic art and architecture / Zulkarnain Yusoff - Yusoff, Zulkarnain (Universiti Teknologi MARA Cawangan Pahang, 1995)
This, paper highlights the early development of Islamic art and Islamic architecture. A particular an is an activity such as drama, poetry, architecture or sculpture in which people try to create something beautiful or to express a particular meaning through their works. However the most important here is a link between an and Islamic doctrine.